2012
DOI: 10.1074/jbc.m112.377333
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of Interacting Regions of the Photoreceptor Phosphodiesterase (PDE6) γ-Subunit with PDE6 Catalytic Dimer, Transducin, and Regulator of G-protein Signaling9–1 (RGS9–1)

Abstract: Background:The PDE6 ␥-subunit serves multiple functions during visual transduction. Results: Several regions of P␥ that interact with PDE6 or transducin were identified. Conclusion: Multiple interacting sites of P␥ with PDE catalytic dimer, transducin, and the transducin/RGS9 complex coordinate the activation and deactivation of PDE6. Significance: This work contributes to understanding how defects in PDE6 structure/function lead to retinal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…One of the key unresolved questions is how the physiological differences between rods and cones can be correlated with the distinctive properties of their phototransduction proteins. Previous studies have shown that the lower thermal stability of cone pigments is likely to contribute to the lower sensitivity of cones but, once activated, rod and cone pigments can couple equally efficiently to rod or cone transducin (Kefalov et al, 2003(Kefalov et al, , 2005Shi et al, 2005Shi et al, , 2007Fu et al, 2008). Thus, consistent with our previous research (Deng et al, 2009) and other studies (Ma et al, 2001), the signaling properties of rod and cone transducin ␣-subunit do not contribute to the difference in light sensitivity between rods and cones (but see Chen et al, 2010).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…One of the key unresolved questions is how the physiological differences between rods and cones can be correlated with the distinctive properties of their phototransduction proteins. Previous studies have shown that the lower thermal stability of cone pigments is likely to contribute to the lower sensitivity of cones but, once activated, rod and cone pigments can couple equally efficiently to rod or cone transducin (Kefalov et al, 2003(Kefalov et al, , 2005Shi et al, 2005Shi et al, , 2007Fu et al, 2008). Thus, consistent with our previous research (Deng et al, 2009) and other studies (Ma et al, 2001), the signaling properties of rod and cone transducin ␣-subunit do not contribute to the difference in light sensitivity between rods and cones (but see Chen et al, 2010).…”
Section: Introductionsupporting
confidence: 81%
“…Overall, it is difficult from our results to gain a clear view of the role of PDE in the differences in sensitivity or kinetics between rods and cones. Interestingly, although rods and cones share the same GAP complex, cones express RGS9 at higher levels (Zhang et al, 2003). This observation, together with the slow inactivation of cone PDE6␣Ј in rods observed by us indicate that, perhaps, the timely T␣*-GTP/PDE complex inactivation in cones requires higher GAP activity than in rods.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The RGS9 gene has been mapped to the identical site as the retinitis pigmentosa gene on chromosome 17 (q23-24) implicating RGS9 as having involvement in degenerative retinal disease (Arshavsky and Wensel, 2013;Granneman et al, 1998;Lai et al, 2013;Sundermeier et al, 2014;Tian et al, 2013;Vincent et al, 2013;Zhang et al, 2012b;Ziccardi et al, 2012). The RGS9 gene produces two major alternatively spliced mRNAs that give rise to substantially different C-termini.…”
Section: Rgs9mentioning
confidence: 97%
“…These biochemical studies are supported by a structure of the PDE5 catalytic domain, in which the M-loop and the α-helix 15 region in the PDE6 catalytic domain were substituted and the resulting chimera complexed with a C-terminal peptide of Pγ (17). Pγ also allosterically regulates the affinity of cGMP binding to the GAFa domain (18, 19), a function that has been localized to a region within the first third of the Pγ sequence (15, 20). Simultaneous interaction of this 87-residue polypeptide with the catalytic site and the GAFa domain suggests a highly extended conformation of Pγ consistent with chemical cross-linking/peptide mapping studies (21) but in marked contrast to the disordered structure of Pγ in solution (22).…”
Section: Introductionmentioning
confidence: 99%